Attenuation of Diabetic Conditions by Sida rhombifolia in Moderately Diabetic Rats and Inability to Produce Similar Effects in Severely Diabetic in Rats - Padmaja Chaturvedi; Tebogo Elvis Kwape (Korean Pharmacopuncture Institute, 2015)
Objectives: This study was done out to evaluate the effects of Sida rhombifolia methanol extract (SRM) on diabetes in moderately diabetic (MD) and severely diabetic (SD) Sprague-Dawley rats. Methods: SRM was prepared by soaking the powdered plant material in 70% methanol and rota evaporating the methanol from the extract. Effective hypoglycemic doses were established by performing oral glucose tolerance tests (OGTTs) in normal rats. Hourly effects of SRM on glucose were observed in the MD and the SD rats. Rats were grouped, five rats to a group, into normal control 1 (NC1), MD control 1 (MDC1), MD experimental 1 (MDE1), SD control 1 (SDC1), and SD experimental 1 (SDE1) groups. All rats in the control groups were administered 1 mL of distilled water (DW). The rats in the MDE1 and the SDE1 groups were administered SRM orally at 200 and 300 mg/kg body weight (BW), respectively, dissolved in 1 mL of DW. Blood was collected initially and at intervals of 1 hour for 6 hours to measure blood glucose. A similar experimental design was followed for the 30-day long-term trial. Finally, rats were sacrificed, and blood was collected to measure blood glucose, lipid profiles, thiobarbituric acid reactive substances (TBARS) and reduced glutathione (GSH). Results: OGTTs indicated that two doses (200 and 300 mg/kg BW) were effective hypoglycemic doses in normal rats. Both doses reduced glucose levels after 1 hour in the MDE1 and the SDE1 groups. A long-term trial of SRM in the MD group showed a reduced glucose level, a normal lipid profile, and normal GSH and TBARS levels. In SD rats, SRM had no statistically significant effects on these parameters. Normal weight was achieved in the MD rats, but the SD rats showed reduced BW. Conclusion: The study demonstrates that SRM has potential to alleviate the conditions of moderate diabetic, but not severe diabetes.